2015
DOI: 10.1016/j.gie.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Novel computer-aided diagnostic system for colorectal lesions by using endocytoscopy (with videos)

Abstract: EC-CAD provides fully automated instant classification of colorectal polyps with excellent sensitivity, accuracy, and objectivity. Thus, it can be a powerful tool for facilitating decision making during routine colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 32 publications
0
108
0
Order By: Relevance
“…Thus, a wide variety of CAD systems are available at present. Importantly, the diagnostic accuracy of these novel methods is higher than that achieved by endoscopic diagnosis by less-experienced endoscopists [9][10][11] .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, a wide variety of CAD systems are available at present. Importantly, the diagnostic accuracy of these novel methods is higher than that achieved by endoscopic diagnosis by less-experienced endoscopists [9][10][11] .…”
Section: Discussionmentioning
confidence: 98%
“…These real-time CAD systems are operated during the actual endoscopic observation. Moreover, Japanese researchers have successfully developed an automated CAD using endocytoscopy based on automated extraction of ultramagnified nuclear features followed by machine-learning analysis from the same group [9][10][11] . Thus, a wide variety of CAD systems are available at present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the computer‐aided diagnosis (CAD) system is gaining attention as an attractive endoscopic diagnostic tool. Some investigators reported that the use of CAD is effective in the management of diminutive and small colorectal polyps . However, participants think that some diminutive or small lesions can be diagnosed only by using WLI.…”
Section: Discussionmentioning
confidence: 99%
“…Their first model was based on automated extraction of nuclear areas stained with methylene blue followed by quantitative analysis of six nuclear features. Their accuracy for identifying neoplastic changes was 89.2% . In their follow‐up study, reported in 2016 and 2018, the diagnostic algorithm was improved by adding texture analysis for feature extraction and a support vector machine as a classifier, thereby producing an output image of the predicted pathology along with the probability of the diagnosis .…”
Section: Automated Polyp Characterizationmentioning
confidence: 99%